KEDALIH - Ni Komang Putriana Agustini; Anak Agung Ketut Oka Adnyana; Ni Nyoman Kasih (Jurnal IGEL : Journal Of Dance, 2025)
Abstract Kedalih is accusation or slander, Rangdaning Jero Agung was accused of killing her husband and slandered by the local community for having black magic so that Randaning Jero Agung's patience ran out, and she meditated at Pura Dalem Blanjong to ask for supernatural powers. And was given supernatural powers, namely Legu Gondong which made the local community restless because of the plague in the form of Legu (mosquitoes). The meaning of "Kedalih" is accusation or slander, so "Kedalih" is a new creative dance work danced by 7 dancers depicting the accusation of Rangdaning Jero Agung who killed her husband so that she became angry, and begged at Pura Dalam Blanjong Sanur to be given supernatural powers, namely Legu Gondong. The Kedalih dance work uses the method of I Kt. Suteja, namely Angripta Sesolahan which consists of the stages of ngarencana, nuasen, makalin, nelesin, and ngebah. The Kedalih work has 3 structural parts accompanied by LIVE Gambelan Semarandana. The makeup used is modified Balinese dance makeup with nuances of clothing taken from the colors White and Black. To realize the Kedalih dance work, the creator chose the partner of the Manubada Art Community, an art community engaged in the field of dance performing arts located in Singapadu Village, Br. Apuan Singapadu. Keywords : Kedalih, Wabah, Nyamuk